A novel MVA-mediated pathway for isoprene production in engineered E. coli. Issue 1 (December 2016) - Yang, Jianming; Nie, Qingjuan; Liu, Hui; Xian, Mo; Liu, Huizhou
Abstract Background To deal with the increasingly severe energy crisis and environmental consequences, biofuels and biochemicals generated from renewable resources could serve as a promising alternative for replacing petroleum as a source of fuel and chemicals, among which isoprene (2-methyl-1, 3-butadiene) in particular is of great significance in that it is an important platform chemical, which has been used in industrial production of synthetic rubber for tires and coatings or aviation fuel. Results We firstly introduced fatty acid decarboxylase (OleTJE ) fromJeotgalicoccus species intoE. coli to directly convert MVA(mevalonate) into 3-methy-3-buten-1-ol. And then to transform 3-methy-3-buten-1-ol to isoprene, oleate hydratase (OhyAEM ) fromElizabethkingia meningoseptica was overexpressed inE. coli . A novel biosynthetic pathway of isoprene inE. coli was established by co-expressing the heterologousmvaE gene encoding acetyl-CoA acetyltransferase/HMG-CoA reductase andmvaS gene encoding HMG-CoA synthase fromEnterococcus faecalis, fatty acid decarboxylase (OleTJE ) and oleate hydratase (OhyAEM ). Furthermore, to enhance isoprene production, a further optimization of expression level of OleTJE, OhyAEM was carried out by using different promoters and copy numbers of plasmids. Thereafter, the fermentation process was also optimized to improve the production of isoprene. The final engineered strain, YJM33, bearing the innovative biosynthetic pathway of isoprene, was found to produce isoprene up to 2.2 mg/L and 620 mg/L under flask and fed-batch fermentation conditions, respectively. Conclusions In this study, by using metabolic engineering techniques, the novel MVA-mediated biosynthetic pathway of isoprene was successfully assembled inE. coli BL21(DE3) with the heterologous MVA upper pathway, OleTJE fromJeotgalicoccus species and OhyAEM fromElizabethkingia meningoseptica . Compared with traditional MVA pathway, the novel pathway is shortened by 3 steps. In addition, this is the first report on the reaction of converting MVA into 3-methy-3-buten-1-ol by fatty acid decarboxylase (OleTJE ) fromJeotgalicoccus species. In brief, this study provided an alternative method for isoprene biosynthesis, which is largely different from the well-developed MEP pathway or MVA pathway.